Comparative Evaluation of Postoperative Epidural Analgesia In Patients Posted For Lower Abdominal And Lower Limb Surgeries With 0.3% Ropivacaine And 0.2% Bupivacaine - Alaspurkar, Nitin R; Chandak, Vijay; Singam, Amol (International Journal of Psychosocial Rehabilitation, 2020)
postoperative epidural analgesia comparison between ropivacaine and bupivacaine